Integration of Muslim Immigrants in Europe and North America: A Transatlantic Comparison. Issue 2 (2nd April 2020) - Liebert, Saltanat; Siddiqui, Mona H.; Goerzig, Carolin
Abstract: Integration of Muslim immigrants has become an increasingly important policy issue in Europe and North America over the last twenty years due to marked growth in the number of Muslim immigrants, the refugee crisis, and the current geopolitical turbulence between Western nations and political Islamist groups. This article explores the factors facilitating and impeding integration of Muslim immigrants in France, the Netherlands, the United States and Canada. Based on the analysis of integration policies and in-depth interviews with integration experts in these four countries, the authors tentatively conclude that equal employment opportunity and social inclusion are key factors that facilitate successful integration of Muslim immigrants. To better integrate its Muslim population, governments are advised to strengthen employment equity laws and implement policies that are more accepting of minority religious practices that foster feelings of inclusivity as well as public campaigns against Islamophobic stereotypes.